Implementation of electro-pneumatic practices learning model based on troubleshooting to improve students' creativity - Septian Eko Cahyanto; Sudji Munadi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study aimed to develop students' creativity through troubleshooting learning models in practical electro-pneumatic. This study was conducted during the Covid 19 pandemic where learning was carried out online. This troubleshooting practice learning is applied to simulation applications so that it can be a solution in implementing learning that cannot be carried out directly. This study used a quasi-experimental researched method with a controlled group pretest-posttest design pattern. The sample consisted of 60 students majoring in mechanical engineering, State University of Semarang was divided into two classes. The experimental class applies the troubleshooting-based practical learned model, while the controlled class implements practice learned without using the troubleshooting learned model. Based on the research result, the pretest mean value in the experimental group was 76.26 with a standard deviation of 11.97, while the pretest mean value in the control group was 74.53 with a standard deviation of 10.31. Meanwhile, the posttest mean score in the experimental group was 77.5 with a standard deviation of 7.62, while the posttest mean score in the control group was 64 with a standard deviation of 8.84. The average post-test score in the experimental group is higher than the control group so it can be concluded that the learning outcomes of the experimental class using a troubleshooting-based practical learning model are higher than the control class where troubleshooting learning models are not implemented in electro-pneumatic practice